Hypernatraemia in South African hospitalised patients - Abohajir, Ali; Rensburg, Megan A; Davids, M Razeen (African Journal of Nephrology, 2019)
Background: Hypernatraemia is a common electrolyte problem in hospitalized patients and is associated with a high mortality rate. We aimed to determine the incidence, causes, management, and outcomes of hypernatraemia in adult hospitalized patients at a large South African tertiary hospital. Methods: A retrospective study was conducted at Tygerberg Hospital in Cape Town, South Africa. Adult patients with hypernatraemia (at least one serum sodium concentration ≥150 mmol/L) during a 3-month period in 2014 were identified from our laboratory database for inclusion. Results: There were 204 patients with hypernatraemia, an incidence of 1.5%. Of these patients, 101 (49.5%) were male, and the mean age was 53 years. There were 66 patients (32.4%) who had hypernatraemia on admission, and 138 who developed it during the course of their hospital stay. The overall in-hospital mortality was 38.7%, with higher rates for older patients and those with more severe degrees of hypernatraemia. Contributory causes which were most commonly present included dehydration/hypovolaemia (45%), followed by sepsis (39%). Net sodium gain, rather than water deficit, was identified as the main mechanism in most of the patients who developed hypernatraemia in the intensive care units. We found little evidence of any diagnostic work-up and also found that the details of fluid therapy and intake-output charting were poorly documented. Conclusions: There is a very high mortality rate in our hospitalized patients with hypernatraemia. The diagnostic work-up and therapy was often inadequate or poorly documented. The management of this important condition needs to be improved with the aid of standardized protocols.